Gender difference of Wharton’s jelly-derived mesenchymal stem cells on differentiation potential into functional granulosa cells: WJ-MSC differentiation into granulosa cell - Lee, Sang-Yun; Bharti, Dinesh; Son, Young-Bum; Lee, Won-Jae; Choe, Yong-ho; Lee, Hyeon-Jeong; Oh, Seong-Ju; Kim, Tae-Seok; Hong, Chae-Yeon; Lee, Sung-Lim; Rho, Gyu-jin (Cellular and Molecular Biology, 2025)
The ovarian follicles consist of theca and granulosa cells, which play a crucial physiological role in sex hormone and cytokine secretion and provide an optimal induction microenvironment for oocytes. However, ethical concerns and the absence of a cellular model for investigating the molecular pathway in humans present challenges for research on granulosa cells. To address these challenges, differentiation induction into granulosa cells using mesenchymal stem cells (MSCs) could offer a novel approach to advancing granulosa cell research. In this study, the granulosa cell differentiation ability and hormone synthesis function of MSCs derived from male and female donors were investigated to identify gender differences. MSCs isolated from Wharton’s jelly (WJ-MSCs) were successfully differentiated into granulosa cell-like cells, as evidenced by the expression of granulosa cell-specific markers at both the mRNA and protein levels. Differentiated WJ-MSCs into granulosa cell-like cells increased aromatase activity, which plays an important role in converting testosterone to estradiol, resulting in significantly increased estradiol levels in differentiated cells compared to undifferentiated WJ-MSCs. However, the activity in female-differentiated cells was significantly higher than in male-differentiated cells. The current study indicates that female-derived WJ-MSCs may represent a novel stem cell resource for understanding granulosa cells and could provide an excellent cellular source for studying various developmental stages and processes of human folliculogenesis.